Challenges and Resources in CPD for In-Service Teachers: Establishing Communities of Inquiry - Pramastiwi, Priska; Lie, Anita; Widiati, Santi; Lie, Trianawaty (Widya Mandala Catholic University Surabaya, 2018)
As teachers are reflective pedagogical thinkers, in-service continuing professional development (CPD) is imperative. Previous studies reveal that insufficient school support and teacher’s incapacity to reflect on their practices recurrently hamper CPD. However, biographical inquiries, encompassing critical events, in-service challenges, and resources employed in CPD, are scant. This study investigated (a) incidents embodying pivotal moments in career choice, (b) ensuing professional challenges, and (c) the resources for CPD at teachers’ disposal. We conducted an in-depth analysis of fifteen Indonesian teachers at novice, mid-career, and senior professional stages. Data from reflective essays and semi-structured interviews disclosed that motivation to teach stems from past experiences indicating intrinsic satisfaction, the influence of significant others, pragmatic concerns, and idealism. Resulting from perennial challenges, including classroom management, lesson planning, and task design, teachers appeared to have benefited most from pre-service teacher training, specifically within the purview of ICT (Information and Communications Technology). A notable finding is that teachers independently sought websites and social media to form professional learning communities, one of which was instigated through the IMOOC (Indonesian Massive Open Online Course). Due to the pervasiveness of technology, this study concludes with recommendations for a conflated model of ICT in CPD to establish communities of inquiry.